Semitic papyrology in context : a climate of creativity : papers from a New York University conference marking the retirement of Baruch A. Levine - Schiffman, Lawrence H. (Culture and history of the ancient Near East ;, 2003)
One of the major and complicating - characteristics of the antique Middle East is the interconnection between the Semitic and Greco-Roman cultures. The current volume brings together studies which relate to the multi-cultural traditions of papyrus writing, with special attention regarding the linguistic, literary, and cultural features of these, often documentary texts. Originally presented at a conference in honour of the retirement of Professor Baruch A. Levine, Skirball Professor Emeritus of Biblical and Ancient Near Eastern Studies (New York University). Important for students of the Greco-Roman world and the Near East in Late Antiquity.